Impact of emergency eLearning in a multilingual context with a minority language: how has the absence of school affected the use of Basque, English, and Spanish in the Basque context?. Issue 10 (26th November 2022) - Idoiaga Mondragon, Nahia; Orcasitas-Vicandi, Maria; Roman Etxebarrieta, Gorka
ABSTRACT : This paper focuses on the use of language during the emergency eLearning period due to Covid-19 in the Basque Autonomous Community. Specifically, the main objective of this study is to analyze how the use of Basque (local minority language), English (foreign language), and Spanish (local majority language) changed during this period among children and the interactions that may exist between them. Four hundred eighty-four teachers and 410 parents participated in this research. The results revealed that teachers perceived a significant decline in the use of Basque that correlated with an increase in the use of Spanish. The decline in the use of Basque was particularly significant among children in kindergarten. The use of English also decreased but was not associated with the use of the other languages. It was also found that the perceptions of children's language use differed between teachers and parents. The findings are explained in terms of assumptions regarding language learning and use in relation to the context of the study. Finally, we discuss some implications of empowering minority and foreign language use in multilingual contexts during emergency eLearning and the measures that should be taken to mitigate the decline in their use at the current time.